Splenic artery embolisation in trauma: A five-year single-centre experience at a UK major trauma centre. (October 2019) - Davies, James; Wells, David
Introduction: Since the introduction of major trauma centres and regional trauma networks in 2012, management of splenic injury has shifted, with non-operative management now favoured. For those requiring intervention, splenic artery embolisation is well established as a first-line treatment in all but the most severely injured. Follow-up is variable, with few guidelines, highlighting the paucity of data addressing the need for further imaging and antimicrobial prophylaxis. This review was undertaken to assess practice and outcomes at our centre in the context of the contemporary literature. Methods: This retrospective study captured splenic embolisations over five years (January 2012–December 2016). CRIS interventional radiology codes were used to retrieve embolisation cases and Trauma Audit and Research Network and hospital event statistics data were used to identify all cases of traumatic splenic injury and to identify splenectomy and non-operative management patients. Outcomes were compared with available standards from different sources. Results: Over the study period 176 splenic injuries were identified, of which 122 underwent non-operative management, 28 were laparotomy first, and 26 undergoing embolisation with an increased trend to an 'embolisation-first' approach over this time. In the embolisation group, the age range was 16–79 yr (mean 41), 18 were male and the median time to intervention was 2 h 9 min (range 1.1–171 h), with eight following failed non-operative management. The proportion of proximal versus selective embolisation versus both was 10:14:1 and the predominant mechanism was coiling. One patient was not embolised due to absence of contrast extravasation on initial angiogram and two proceeded to splenectomy due to failure of splenic artery embolisation. There were complications in six patients: five ongoing left upper quadrant pain, one infected haematoma requiring drainage, two chest infections with pleural effusions, one of which required drainage. There were two deaths from other injuries. Fifteen of the 25 patients who underwent splenic artery embolisation had follow-up imaging, seven did not and three were excluded due to splenectomy and/or death; five patients were vaccinated according to the hospital splenectomy protocol, and six received prophylactic antibiotics. Conclusion: Our data show that non-operative management is the mainstay of treatment for the majority of splenic injury patients. Serious complications are not common but variation does exist in follow-up. The changing management trends are in line with national data. These findings will help to further implement and develop local protocols but more work is required to address splenic function after embolisation and the requirement for antimicrobial prophylaxis.